Kidnapping intergroup young: an alternative strategy to maintain group size in the group-living pied babbler (Turdoides bicolor). (23rd May 2022) - Ridley, Amanda R.; Nelson-Flower, Martha J.; Wiley, Elizabeth M.; Humphries, David J.; Kokko, Hanna
Abstract : Both inter- and intragroup interactions can be important influences on behaviour, yet to date most research focuses on intragroup interactions. Here, we describe a hitherto relatively unknown behaviour that results from intergroup interaction in the cooperative breeding pied babbler: kidnapping. Kidnapping can result in the permanent removal of young from their natal group. Since raising young requires energetic investment and abductees are usually unrelated to their kidnappers, there appears no apparent evolutionary advantage to kidnapping. However, kidnapping may be beneficial in species where group size is a critically limiting factor (e.g. for reproductive success or territory defence). We found kidnapping was a highly predictable event in pied babblers: primarily groups that fail to raise their own young kidnap the young of others, and we show this to be the theoretical expectation in a model that predicts kidnapping to be facultative, only occurring in those cases where an additional group member has sufficient positive impact on group survival to compensate for the increase in reproductive competition. In babblers, groups that failed to raise young were also more likely to accept extragroup adults (hereafter rovers). Groups that fail to breed may either (i) kidnap intergroup young or (ii) accept rovers as an alternative strategy to maintain or increase group size. This article is part of the theme issue 'Intergroup conflict across taxa'.